Effects of zinc amino acid complex on biomarkers of gut integrity and metabolism during and following heat stress or feed restriction in pigs. (25th September 2018) - Mayorga, Edith J; Kvidera, Sara K; Horst, Erin A; Al-Qaisi, Mohmmad; Dickson, Mackenzie J; Seibert, Jacob T; Lei, Samantha; Keating, Aileen F; Ross, Jason W; Rhoads, Robert P; Rambo, Zachary J; Wilson, Mark E; et al.
Abstract: Study objectives were to determine the effects of zinc (Zn ) amino acid complex (Availa Zn, Zinpro Corporation, Eden Prairie, MN) on metabolism, biomarkers of leaky gut, and inflammation during and following heat stress (HS ) and nutrient restriction. Crossbred gilts ( n = 50; 50 ± 2 kg BW) were blocked by initial BW and randomly assigned to one of five treatments: 1) thermoneutral (TN ) and ad libitum fed a control diet (TNCtl ), 2) TN and pair-fed a control diet (PFCtl ), 3) TN and pair-fed a Zn-supplemented diet (PFZn ), 4) HS and ad libitum fed a control diet (HSCtl ), and 5) HS and ad libitum fed a Zn-supplemented diet (HSZn ). The study consisted of 3 experimental periods (P): during P1 (7 d), all pigs were fed their respective diets ad libitum and housed in TN conditions (20.84 ± 0.03 °C, 47.11 ± 0.42% relative humidity). During P2 (7 d), HSCtl and HSZn pigs were exposed to progressive cyclical HS conditions (27 to 30 °C, 41.9 ± 0.5% relative humidity), while TNCtl, PFCtl, and PFZn pigs remained in TN conditions and were fed ad libitum or pair-fed to their respective HSCtl and HSZn counterparts. During P3 (5 d; "recovery phase"), all pigs were housed in TN conditions and fed ad libitum. Pigs exposed to HS had overall increased rectal temperature, skin temperature, and respiration rate (0.33 °C, 3.76 °C, and 27 bpm, respectively; P < 0.01). Relative to TN controls, HS decreased ADFI and ADG (28 and 35%, respectively; P < 0.05), but these variables were unaffected by dietary treatment. Additionally, circulating insulin did not differ between HS and TN pigs ( P = 0.41), but was decreased in PF relative to TN pigs ( P < 0.01). During recovery, no differences were observed in rectal temperature or respiration rate across treatments, but HSZn pigs had decreased skin temperature relative to TN, PF, and HSCtl pigs ( P < 0.01). During P3, no Zn effects were observed in production parameters; however, PF pigs had increased ADFI and ADG relative to TN and HS treatments ( P < 0.01). During P3, circulating insulin was increased in pigs that were HS relative to TN and PF pigs (75%, P < 0.05). Interestingly, tumor necrosis factor alpha (TNFα ) levels were decreased during P3 ( P = 0.04) in Zn relative to Ctl-fed pigs. Circulating lipopolysaccharide-binding protein was not different among periods ( P > 0.10). In summary, Zn reduced TNFα (regardless of HS), and the stimulatory effect of HS on insulin secretion is amplified during HS recovery.